Utilization of financial assistance under Janani Suraksha Yojna in Rural North India - Malik, Jagbir; Kalhan, Meenakshi; Punia, Anita; Behera, Binod (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context: Janani Suraksha Yojna (JSY), a conditional cash transfer scheme aims to encourage women to deliver their babies in medical facilities.Aims:To study the utilization of financial assistance under JSY. Settings: Rural areas of Haryana.Study Design:Cross-sectional study. Participants: Mothers who delivered within last 12 months (January to December 2010) and were entitled for benefits under JSY. Subjects and Methods: This cross-sectional study was conducted in two districts of Haryana. One district each was selected randomly from amongst high and low performing districts, depending upon rate of institutional deliveries. A total of 48 sub-centers were selected by multistage random sampling. Out of the 1476 enlisted JSY beneficiaries, 1386 mothers were interviewed by house-to-house visits, after getting informed consent. Data were collected on a pre-designed, pre-tested, semi-structured questionnaire, and analyzed using the SPSS (version 17.0). Results: About 14% (n= 189) mothers had not received the financial assistance until the time of interview. Only 7.6% mothers got the financial assistance within 1 month after delivery. In nearly half (48.8%) study subjects, financial assistance was delayed beyond 3 months after delivery. More than half (52.7%) got the JSY assistance in cash and 34.8% by check. The incentive was not properly utilized as it was given to the family pool (70.2%) or put in savings account (5%). Only in about one-fifth of mothers, it was used for mother’s care (I7.8%) and child care (5.8%). Conclusion: JSY is an ambitious scheme serving as a safe motherhood intervention under the National Rural Health Mission. It has been reasonably successful in promoting institutional deliveries, but the discrepancy in payment of funds was found in home deliveries as well as institutional deliveries. Therefore, the program managers should make the monitoring system for disbursement of funds more effective.